2010
DOI: 10.1002/app.33028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and flame retardant properties of ethylene‐vinyl acetate copolymer/modified multiwalled carbon nanotube composites

Abstract: The synthesized flame retardant 9,10-dihydro-9-oxa-10-phosphaphanthrene-10-oxide/vinyl methyl dimethoxysilane (DV) was used to modify multiwalled carbon nanotubes (MWNTs). The results of FTIR, 1 H-NMR, and TGA measurements show that DV has been covalently grafted onto the surfaces of MWNTs, and the MWNTs-g-DV is obtained successfully. Transmission electron microscopy images show that a core-shell nanostructure appears with MWNTs as the core and the DV thin layers as the shell, and the modified MWNTs with DV ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Moreover, no decomposition occurs beyond 425 °C for any of the materials, which indicates that a more thermally stable char could be generated at 425 °C after adding OCNTs. This finding could be attributed to the formation of a carbon layer on the surface of the samples 28 . These significant enhancements in decomposition temperatures are attributed to the synergetic effect between LDHs and CNTs.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, no decomposition occurs beyond 425 °C for any of the materials, which indicates that a more thermally stable char could be generated at 425 °C after adding OCNTs. This finding could be attributed to the formation of a carbon layer on the surface of the samples 28 . These significant enhancements in decomposition temperatures are attributed to the synergetic effect between LDHs and CNTs.…”
Section: Resultsmentioning
confidence: 87%
“…This covers the entire surface of the sample without forming any significant cracks. Other studies have demonstrated that the dense network of nonflammable CNTs acts as a physical barrier to the diffusion of oxygen and also slows the escape of combustion products formed during decomposition, which can shield the polymer resin from external radiation and heat feedback from the flame 26 27 28 . However, although CNTs have shown good potential in flame retardancy their dispersion within the polymer matrix is normally poor, due to their hydrophilic nature.…”
mentioning
confidence: 99%
“…The most widely studied nanofiber materials with respect to polymer fire retardancy are carbon nanotubes (CNTs) . Flame retardant properties of CNTs were studied in poly(ethylene vinyl acetate) , PMMA , unsaturated polyester , polyether ether ketone , and so on. Another group of nanoparticles, which can be used as fire retardant additives, are metal oxides, silica, and polyhedral oligomeric silsesquioxane .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the fire performance often involves quantifying heat generation and smoke generation, as the rate of smoke production (SPR) [32]. It can be seen in values of EOS1-EOS4 gradually decreased with more added SiO 2 , and the reduction was most evident for EOS4.…”
Section: Spr Of the Eva/os/sio 2 Compositesmentioning
confidence: 99%